PSYCHOLOGICAL CHALLENGES OF ELDERS IN GONDAR, NORTH WEST ETHIOPIA - GEBRESILUS, asfaw getnet; yizengaw, simegn sendek (Innovare Journal of Social Sciences, 2014)
Abstract Elders in Ethiopia are vulnerable to diversified psychological problems due to multifaceted challenges like elderly abuse, stereotypes, myths and lack of psychosocial support. As a result, they are triggered to develop versatile psychological problems. The main objective of this study was to examine psychological challenges (anxiety, depression, self-esteem and loneliness) among elders who were residing in Gondar City. For this purpose, 124 study participants were selected using snowball sampling technique. In order to assess the level of self-esteem, Rosenberg self-esteem inventory was used. Anxiety and depression were assessed using depression symptoms inventory and loneliness was assessed through UCLA Loneliness Scale. Then, analysis was made using t-test, ANOVA and correlation. The study revealed statistically significant sex difference on anxiety (p<0.05) but not on self-esteem, depression and loneliness (p>0.05). Concerning marital status statistically significant difference was found on self-esteem, loneliness, anxiety, and depression (p<0.05). In addition, significant variation was detected with type of primary care givers on self-esteem, loneliness, anxiety and depression (p<0.05). Regarding, educational status, statistically significant variation was seen on loneliness and depression (p<0.01) but not on self-esteem and anxiety (p>0.05). Self-esteem was statistically significant inverse relationship with age (p<0.01), and direct relationship with income level (p<0.01). Furthermore, age was statistically significant relationship with loneliness, (p<0.01), anxiety (p<0.05) and depression (p<0.01). Based on the findings researchers concluded that regardless of the variation in sex elders are vulnerable to psychological problems; independent life, marital status, age and income level are associated with psychological problems. Keywords:Â Â Â Anxiety; Depression; Elders; Loneliness; Self-esteem